Canadian Stroke Best Practice Recommendations: Managing transitions of care following Stroke, Guidelines Update 2016. Issue 7 (October 2016) - Cameron, Jill I; O'Connell, Colleen; Foley, Norine; Salter, Katherine; Booth, Rhonda; Boyle, Rosemary; Cheung, Donna; Cooper, Nancy; Corriveau, Helene; Dowlatshahi, Dar; Dulude, Annie; Flaherty, Patti; et al.
Every year, approximately 62, 000 people with stroke and transient ischemic attack are treated in Canadian hospitals. For patients, families and caregivers, this can be a difficult time of adjustment. The 2016 update of the Canadian Managing Transitions of Care following Stroke guideline is a comprehensive summary of current evidence-based and consensus-based recommendations appropriate for use by clinicians who provide care to patients following stroke across a broad range of settings. The focus of these recommendations is on support, education and skills training for patients, families and caregivers; effective discharge planning; interprofessional communication; adaptation in resuming activities of daily living; and transition to long-term care for patients who are unable to return to or remain at home. Unlike other modules contained in the Canadian Stroke Best Practice Recommendations (such as acute inpatient care), many of these recommendations are based on consensus opinion, or evidence level C, highlighting the absence of conventional evidence (i.e. randomized controlled trials) in this area of stroke care. The quality of care transitions between stages and settings may have a direct impact on patient and family outcomes such as coping, readmissions and functional recovery. While many qualitative and non-controlled studies were reviewed, this gap in evidence combined with the fact that mortality from stoke is decreasing and more people are living with the effects of stroke, underscores the need to channel a portion of available research funds to recovery and adaptation following the acute phase of stroke.